Sixteen Years of Appreciative Conversation: The Building Bridges Seminar in Retrospect (American Journal of Islam and Society, 2017)
January 2002 saw the launch of several interfaith initiatives from the officeof the Archbishop of Canterbury, the spiritual leader of the worldwide AnglicanCommunion. Of these, the Building Bridges Seminar has sustaineditself the most vigorously and has borne the most fruit. Founded out of thesense of urgency following the events of September 11, 2001, and nowhaving met sixteen times, the seminar has been described from its inceptionas an exercise in “appreciative conversation” made possible by “listeningwith openness and mutual respect” and characterized by “courage, grace,imagination and sensitivity in addressing and retreating from painful issues.”1 Presented below is a brief description of its history, methodology,and impact.